2016
DOI: 10.1002/jmri.25256
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the quantitative evaluation of diffusion‐weighted mri in the diagnosis of anterior cruciate ligament tears

Abstract: The CNRs of the torn ACL with each b value (600 and 1000) were significantly higher those of than normal ligament, although the ADC values of the torn ligament were not different from normal ligament. Addition of the DWI to the conventional MRI did not improve diagnostic performance. J. Magn. Reson. Imaging 2016;44:1116-1122.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…However, this study was limited to the qualitative use of DWI. Park et al 46 evaluated the feasibility of quantitative DWI in the diagnosis of ACL rupture. These authors found no additional benefit of DWI to differentiate between ruptured and normal ACLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study was limited to the qualitative use of DWI. Park et al 46 evaluated the feasibility of quantitative DWI in the diagnosis of ACL rupture. These authors found no additional benefit of DWI to differentiate between ruptured and normal ACLs.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al 46 ACL reconstruction. This factor may account for the relatively high failure rates reported in most studies.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas MRI is a very reliable tool in the acute and chronic setting for complete ACL tear and concomitant injuries [ 17 , 18 ], partial ACL tears are less obviously recognized on conventional morphologic sequences, especially in a chronic setting [ 19 , 20 ]. Whereas functional sequences as diffusion weighted imaging MRI may not improve diagnosis [ 21 , 22 ], stress MRI are a valuable tool to visualise translatory and rotatory instability [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%